Representasi Budaya Timur dan Barat dalam Novel Eat Pray Love - Dyah Kristyowati; Agnes Setyowati Hariningsih (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
AbstractEat Pray Love's novel by Elizabeth Gilberth tells the story of a woman's journey by herself in three countries for one year. She visited Italy, India and Indonesia. Her purpose of journey is to find a balance in her life. It can be seen from the interaction between characters and conflicts contained in this novel. Her trip to Italy is to explore the art of fun. She explores the art of meditation and devotion in the country of India and the balance in Bali Indonesia. Representation of Western and Eastern Culture is well defined in the novel Eat Pray Love. Representation of Eastern Culture represented by India and Indonesia and the West represented by Italian culture will be analyzed more deeply in this study. The final result of this research is to find out about the Representation of Italian, Indian and Indonesian Culture in the novel Eat Pray Love by Elizabeth Gilberth. In this study the writer focuses on the analysis of Cultural Representation analysis uses cultural theory through the analysis of cultural elements such as language, knowledge systems, social organizations, living equipment systems and technology, livelihood systems, religious systems, and arts.Keywords: culture, cultural representation, cultural elements, Italy, India, Indonesia